It's okay to talk: suicide awareness simulation. (18th June 2019) - Phillips, Emma Claire; Neagle, Gregg; Cameron, Bethan; Moneypenny, Michael
Summary: Background: Doctors are at an increased risk of suicide compared with the general population, and there is a current lack of formal education on suicide prevention for peers and colleagues. This educational project aimed to increase suicide awareness for medical students through simulation. Methods: A simulation scenario was designed centred around a junior doctor (a qualified doctor who has not yet completed specialist postgraduate training) disclosing thoughts of suicide. The scenario and debriefing were designed using learning objectives and constructive alignment theory. Senior medical students participated in the scenario, which was followed by a facilitated debriefing and the provision of a framework for discussing suicide with a colleague. Quantitative and qualitative student feedback was collected and analysed. A simulation scenario was designed centred around a junior doctor colleague found distressed at work and disclosing thoughts of suicide Results: A total of 35 students participated in the simulation over six sessions. Feedback indicated that students felt this subject was important and that the learning objectives had been achieved. Discussion: This simulation scenario focusing on suicide awareness for senior medical students has provided opportunity for open discussion and reflection on the topic and has increased the awareness and understanding of suicidality in colleagues. This is one step in the direction of preventing further deaths by suicide in health professionals.